Polymorphism of the Introduced Snail Cepaea nemoralis (Gastropoda, Helicidae) from two Distant Parts of Eastern Europe: Accidental Similarity or Regularity? - Gural-Sverlova, N. V.; Gural, R. I. (Publishing House "Akademperiodyka" of the National Academy of Sciences of Ukraine, 2021)
The shell coloration of Cepaea nemoralis from Western Ukraine (Ivano-Frankivsk, Lviv, and Ternopil regions) and from the Moscow region of Russia was analyzed, in total, almost 6 thousand specimens from 32 sites. In the samples from the Moscow region, on average, there were half as many yellow shells and four times as many pink mid-banded shells. There were no other statistically significant differences. As in other areas of Eastern Europe, yellow unbanded and brown shells were often absent or represented by few individuals in both compared areas, and brown banded shells were completely (Western Ukraine) or almost completely (Moscow region) absent, which may be related to the founder effect. Analysis of the literature data showed that in the introduced populations of C. nemoralis from Europe and USA, a distinct predominance of one or two of the 4 light phenotypes (yellow unbanded, yellow mid-banded, pink unbanded, and pink mid-banded) is often observed. The total frequency of these phenotypes in introduced populations is often higher than its average values calculated for different parts of the natural range. A possible relationship between the observed pattern and climatic selection is discussed.